2015
DOI: 10.1007/s10853-015-9458-2
|View full text |Cite
|
Sign up to set email alerts
|

Porous self-protonating spiropyran-based NIPAAm gels with improved reswelling kinetics

Abstract: This study focuses on improving the speed of actuation of poly(N-isopropylacrylamide)-based photoresponsive gels containing copolymerised spiropyran as the photoswitch and acrylic acid as the proton source. The improvement is realised by introducing pores into the material. For this purpose, polyethylene glycol (PEG) of two molecular weights (2,000 and 20,000 g mol -1 ) has been used as the porophore in the polymerisation mixture. Upon removal of the PEG porophore post polymerisation, hydrogels of different po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 41 publications
(69 reference statements)
0
29
1
Order By: Relevance
“…Previous work on spiropyran photochromic systems include their use for photo-induced optical sensing of metal ions, continuous flow optical sensing of solvents of different polarity [23,24], reversible photo-actuators for microfluidic applications [25][26][27], photo-chemopropulsion of microdroplets [28], and self-assembly [29,30], among others. More recently it was demonstrated that the conversion between the SP and MC form can be achieved also mechanically under tensile loading, showing the capability to create mechanochromic materials using SP containing polymers [31].…”
Section: Introductionmentioning
confidence: 99%
“…Previous work on spiropyran photochromic systems include their use for photo-induced optical sensing of metal ions, continuous flow optical sensing of solvents of different polarity [23,24], reversible photo-actuators for microfluidic applications [25][26][27], photo-chemopropulsion of microdroplets [28], and self-assembly [29,30], among others. More recently it was demonstrated that the conversion between the SP and MC form can be achieved also mechanically under tensile loading, showing the capability to create mechanochromic materials using SP containing polymers [31].…”
Section: Introductionmentioning
confidence: 99%
“…Responsive micromixers that change shape using light as a stimulus would be appealing, as it allows to control mixing, in a noninvasive, noncontact fashion . Hydrogels such as poly‐ N ‐isopropylacrylamide (pNIPAAM) have received a lot of attention, as the shape can be changed from a swollen to a collapsed state with temperature . This shape change can also be achieved using light by incorporation of a photochromic dye in the polymer hydrogel .…”
Section: Introductionmentioning
confidence: 99%
“…[18,26,27] Hydrogels such as poly-N-isopropylacrylamide (pNIPAAM) have received a lot of attention, as the shape can be changed from a swollen to a collapsed state with temperature. [28][29][30][31][32][33] This shape change can also be achieved using light by incorporation of a photochromic dye in the poly mer hydrogel. [34][35][36][37][38] Upon switching the illumination on and off, [39] the volume of the hydrogel can be switched between two states.…”
Section: Introductionmentioning
confidence: 99%
“…This kind of skin layer should induce slower response rate, structural disorders, and functional decline of the gel, which should limit the drug diffusing out of gels . Creating the pores inside the gels is considered as an effective method for solving this problem and improve the deswelling rate of gels, since that the water or drug could flow into/out of the porous gels by convection through the pores rather than diffusion through the gel network . Moreover, the porous structure inside the gels could increase the space and surface area, which allows more drugs to be loaded inside the gels, it is also important to an applicable drug carrier.…”
Section: Introductionmentioning
confidence: 99%